2008
DOI: 10.1523/jneurosci.4407-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 Protects against Ischemic Brain Injury via Attenuation of a Novel Stress-Response Cascade Upstream of Mitochondrial Cell Death Signaling

Abstract: Heat shock protein 27 (Hsp27), a recently discovered member of the heat shock protein family, is markedly induced in the brain after cerebral ischemia and other injury states. In non-neuronal systems, Hsp27 has potent cell death-suppressing functions. However, the mechanism of Hsp27-mediated neuroprotection has not yet been elucidated. Using transgenic and viral overexpression of Hsp27, we investigated the molecular mechanism by which Hsp27 exerts its neuroprotective effect. Overexpression of Hsp27 conferred l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
154
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(172 citation statements)
references
References 77 publications
14
154
0
1
Order By: Relevance
“…Under physiological conditions, the level of HSP27 is extremely low in the brain; however, HSP27 expression is transiently induced in brain glial cells and/or ECs at 24 h or later following cerebral I/R (14). Previous studies by our and other groups demonstrated robust neuroprotective effects of HSP27 overexpression against I/R brain injury (15)(16)(17)(18), which were largely credited to its antiapoptotic actions. However, HSP27 exerts additional actions on ECs (14).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Under physiological conditions, the level of HSP27 is extremely low in the brain; however, HSP27 expression is transiently induced in brain glial cells and/or ECs at 24 h or later following cerebral I/R (14). Previous studies by our and other groups demonstrated robust neuroprotective effects of HSP27 overexpression against I/R brain injury (15)(16)(17)(18), which were largely credited to its antiapoptotic actions. However, HSP27 exerts additional actions on ECs (14).…”
mentioning
confidence: 79%
“…We previously reported that transgenic mice with ubiquitous overexpression of HSP27 developed significantly less brain damage after cerebral I/R, including less BBB disruption (17,18,22). These beneficial effects of HSP27 were attributed mainly to its well-characterized antiapoptotic functions Fig.…”
Section: Ec-specific Overexpression Of Hsp27 Ameliorates Bbb Disruptionmentioning
confidence: 98%
“…Heat-shock protein 27 (HSP27) protects neurons during cerebral ischemia [65] through phosphorylation at Ser15 and Ser82, critical sites for neuroprotection. PKD also directly phosphorylates HSP27 [66] .…”
Section: Role Of Pkd In Neuroprotectionmentioning
confidence: 99%
“…As PKCÎŽ directly phosphorylates PKD1 in vivo, PKCÎŽ loss-of-function may effectively inhibit PKD1 activation. It is worth noting that PKD1 loss-of-function by RNAi or overexpression of S916APKD1 enhances oxidative stress-induced apoptosis, while PKD1 gain-of-function inhibits this apoptosis [64] .Heat-shock protein 27 (HSP27) protects neurons during cerebral ischemia [65] through phosphorylation at Ser15 and Ser82, critical sites for neuroprotection. PKD also directly phosphorylates HSP27 [66] .…”
mentioning
confidence: 99%
“…Similarly, using a model of transient cerebral ischemia, HSP27 transgenic mice have been shown to develop a reduced infarct size (Stetler et al 2008).…”
Section: Introductionmentioning
confidence: 99%